Development of quantum dot solar cells for clean energy - Alexander John Potter (2011)
This report compiles all the works done by the author in relation to his Final Year Project choice as part of the course requirements of the School of Electrical & Electronic Engineering at Nanyang Technological University, and covers one main project.